The Impact of Product Assortment Framing on The Attitude Toward Gift Set - Ma, Juhuy; Kim, Gwi-Gon (International Journal of Membrane Science and Technology, 2024)
The purpose of this paper is to study how consumers’ attitudes toward different types of product assortment and Unpacking Framing under the moderating effects of consumption situation, prior knowledge of products, and involvement. Results are based on a survey with 344 respondents. The results indicate that consumers favor a diverse product assortment over a simple one. Second, if the consumer buys the product as a gift, they favor a more diverse product assortment, however, if the consumer buys it to consume by themselves, diversification or simplification of product assortment does not matter. Third, in the case of diverse product assortment, consumer favors detailed message framing over comprehensive one. Fourth, in the case of high prior knowledge, the consumer favors a detailed description of the product. Furthermore, there is no such difference in the case of low prior knowledge.